Pengaruh Komunikasi Persuasif Beauty Vlogger di Youtube Terhadap Minat Beli Konsumen - Annisa Aulia; Risa Dwi Ayuni; Adelia Winda Hapsari (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This research is based on the phenomenon of the rise of influencers that have sprung up on social media by focusing on how to communicate beauty influencers on Youtube social media or better known as Beauty Vloggers with its followers.  These beauty vloggers are invited to work together in promoting a product to improve the brand image to the target sales of the brand company concerned.  In its performance in promoting the product, Beauty Vlogger as a trendsetter affects its audience by communicating persuasively wrapped in the word product review as a form of promoting it.  The way they communicate this will later affect the audience response to be interested to buy a product.  Research uses a quantitative method approach.  The data analysis used is a simple linear regression analysis model with the population in this study is the viewer of the Beauty Vlogger video on YouTube, especially on the @livjunkie channel.  The number of samples in this study was 100 respondents, the results were obtained based on calculations using the Slovin formula on the number of followers of the @livjunkie channel.  The results of this study indicate the influence of persuasive communication by beauty vlogger on consumer buying interest.  This result was obtained based on the coefficient of determination with a value of 62.1% which indicated that variable X had a significant and positive effect on the Y variable.